To solve the system of equations, we'll first substitute the second equation \( x = 5y - 1 \) into the first equation \( 2x + 6y = -18 \).
-
Substitute \( x \) in the first equation: \[ 2(5y - 1) + 6y = -18 \]
-
Distribute the 2: \[ 10y - 2 + 6y = -18 \]
-
Combine like terms: \[ 16y - 2 = -18 \]
-
Add 2 to both sides: \[ 16y = -16 \]
-
Divide by 16: \[ y = -1 \]
Now substitute \( y \) back into the second equation to find \( x \): \[ x = 5(-1) - 1 = -5 - 1 = -6 \]
The solution to the system of equations is \( (x, y) = (-6, -1) \).
Therefore, the correct response is: \[ \text{(−6, −1)} \]